A case of mistaken identity: An unusual presentation of neoplastic meningitis and a reminder of the hallmark features. Issue 12 (15th September 2020) - Davidson, Catriona; Achilleos, Katerina; Crawley, Francesca; Petchey, William
Abstract: This case offers an opportunity for education on the manifestations of neoplastic meningitis, a revision of the hallmark investigative features, and a reminder of the utilization of lumbar puncture in investigating unexplained neurological symptoms. Additionally, it emphasises the need for clinicians to avoid "diagnostic anchoring" when faced with recurrent attenders. Abstract : This case offers an opportunity for education on the manifestations of neoplastic meningitis, a revision of the hallmark investigative features, and a reminder of the utilization of lumbar puncture in investigating unexplained neurological symptoms. Additionally, it emphasises the need for clinicians to avoid "diagnostic anchoring" when faced with recurrent attenders.